EPISTEMOLOGI DAN PRAKTIK SAINS: MEMAHAMI PERAN FILSAFAT ILMU DALAM PENGEMBANGAN PENGETAHUAN - Mardinal Tarigan; Kevin Alfansyah (JIP: Jurnal Ilmu Pendidikan, 2023)
In the context of scientific research, an understanding of the epistemology of science is essential to uncover how science acquires valid and reliable knowledge. The practice of science, as the concrete steps in conducting research, includes the methods, procedures, and ethics that form the basis for knowledge development. However, an understanding of the practice of science and the epistemology of science cannot be separated from the influence of the philosophy of science. Philosophy of science helps to understand the nature of scientific knowledge, to address questions about the resources and limits of science, and to provide a conceptual framework for the development of knowledge. In this context, this research explores the role of philosophy of science in shaping the understanding and practice of science and its implications for the development of knowledge. The research provides important insights for scientists and practitioners in understanding how philosophy of science provides a strong conceptual foundation for the development of scientific knowledge.